Mapping Agroforestry area in India through remote sensing and preliminary estimates - Rizvi, R.H.; Dhyani, S. K.; Newaj, Ram; Karmakar, P. S.; Saxena, A. (Indian Farming, 2015)
Agroforestry will play a major role in coming years, not only for Indian Farming 64 February 2014 importance in food and livelihood security but also for its role in combating environmental challenges. In order to harness its potential, an accurate estimation of extent of area under agroforestry in the country is required. The accurate assessment of area under agroforestry systems in India can be done with the help of geospatial technologies. These preliminary estimates will have to be verified once proposed methodology for agroforestry mapping using geospatial technologies has been developed.